Timbral Spectogram of The Bonang From Malaysian Gamelan - Sinin, Hamdan; Ahmad Fauzi, Musib; Iran Amri, Musoddiq; Hasnizam, Abdul Wahid; Saiful Hairi, Othman (The International Journal of Innovative Design, Creativity and Social Sciences, 2018)
This study explores timbral visualization to recognize the sound from Malaysian Gamelan and provide detailed description of the sound.The timbre of two sets of bonang (bonang penerus and bonang barung ) are used to perceive the sound recorded from the Malaysian Gamelan. The higher pitch bonang penerus are smaller in size than the bonang barung . The bonang panerus plays a part that is similar to the bonang barung with frequency twice as bonang barung .The timbral characteristics can precisely and objectively describes the sound characteristics of aboning that was always faced by ethnomusicologists in field work activities. The sound profile from each set of boning shows different characteristics which indicate that the recognition process showed a high recognition rate. From the finding bonang penerus showed a clear fundamental frequency indicated by the brightest colors’ in the spectrogram (yellow and red). Bonang barung showed a strong attack and decay rapidly.The sustainability or the rapid decay is also indicated by the Q factor.Q factor for bonang penerus range from 20.20 to 23.87 whereas the Q factor for bonang barung is slightly small from 12.70-17.00.